Estado emocional y su incidencia en el proceso de enseñanza - aprendizaje de los estudiantes de la Escuela de Educación Básica Isabel La Católica en la ciudad de Babahoyo - Isa Bravo, Cindy Lorena (2023)
The present non-experimental study was carried out at the Isabel la Católica School of basic education. It seeks to explain the emotional states and their incidence in the teaching-learning process in children of the Isabel la Católica School in Babahoyo. To achieve the purpose of this study, an exhaustive bibliographic review was made on the variables addressed and a series of instruments such as structured surveys were used, which will allow gathering information on the subject in question, also the application of psychometric test, mesquite test and Baron test was executed to determine the main indicators of problems regarding their emotional intelligence and how it affects their emotional state and also interviews with teachers will be applied to know the way they face the emotional part of themselves and their students in the classroom. The sample is non-probabilistic and is composed of 40 children specifically, who answered affirmatively to questions related to emotional states and through the tests there was evidence of altered emotional states. It was found that the emotional states expressed by most of the students were: sadness, dissatisfaction, anger.